Probiotics for preventing and treating infant regurgitation: A systematic review and meta‐analysis. Issue 1 (15th December 2021) - Foster, Jann P.; Dahlen, Hannah G.; Fijan, Sabina; Badawi, Nadia; Schmied, Virginia; Thornton, Charlene; Smith, Caroline; Psaila, Kim
Abstract: Infant regurgitation is common during infancy and can cause substantial parental distress. Regurgitation can lead to parental perception that their infant is in pain. Parents often present in general practitioner surgeries, community baby clinics and accident and emergency departments which can lead to financial burden on parents and the health care system. Probiotics are increasingly reported to have therapeutic effects for preventing and treating infant regurgitation. The objective of this systematic review and meta‐analysis was to evaluate the efficacy of probiotic supplementation for the prevention and treatment of infant regurgitation. Literature searches were conducted using MEDLINE, CINAHL, and the Cochrane Central Register of Controlled trials. Only randomised controlled trials (RCTs) were included. A meta‐analysis was performed using the Cochrane Collaboration methodology where possible. Six RCTs examined the prevention or treatment with probiotics on infant regurgitation. A meta‐analysis of three studies showed a statistically significant reduction in regurgitation episodes for the probiotic group compared to the placebo group (mean difference [MD]: −1.79 episodes/day: 95% confidence interval [CI]: −3.30 to −0.27, N  = 560), but there was high heterogeneity (96%). Meta‐analysis of two studies found a statistically significant increased number of stools per day in the probiotic group compared to the placebo group at 1 month of age (MD: 1.36, 95% CI: 0.99 to 1.73, N  = 488), with moderate heterogeneity (69%). Meta‐analysis of two studies showed no statistical difference in body weight between the two groups (MD: −91.88 g, 95% CI: 258.40–74.63: I 2  = 23%, N  = 112) with minimal heterogeneity 23%. Probiotic therapy appears promising for infant regurgitation with some evidence of benefit, but most studies are small and there was relatively high heterogeneity. The use of probiotics could potentially be a noninvasive, safe, cost effective, and preventative positive health strategy for both women and their babies. Further robust, well controlled RCTs examining the effect of probiotics for infant regurgitation are warranted. Abstract : Key messages: Infant regurgitation is common during infancy and can cause substantial parental distress. The currently available evidence does not support or refute the efficacy of probiotics for the prevention and treatment of infant regurgitation but data from the individual trials and subset meta‐analysis of studies are promising. There are no indications from the available data that probiotics have any adverse effects. Further well‐controlled RCTs are warranted to investigate the efficacy of various strains and species, dosage, and combinations of probiotics.